Pola Perubahan Kemampuan Argumentasi Ilmiah melalui Model Pembelajaran Kontekstual Multirepresentasi - Lenny Agustina Suwastika Sari; Markus Diantoro; Muhardjito Muhardjito (Graduate School of Universitas Negeri Malang, 2019)
Abstract: This study aims to determine the ability of scientific argumentation of students. The study was conducted on 64 of students X-MIPA class on force and motion. The results of the observation showed that the argument ability of the concept force and motion in students was still very low. The low ability of participants' scientific arguments could also influenced by inappropriate learning models. The learning model applied is a multi-representation based contextual learning model was implemented. The results showed that there was an improve in the ability of scientific argumentation after applying a multi-presentation based contextual learning model. Analysis obtained was 0% at level 17.18% at level 43.75% at level 37.13% at level 4 and 10.94% at level 5.Abstrak: Penelitian ini bertujuan untuk mengetahui kemampuan argumentasi ilmiah siswa. Penelitian dilakukan pada 64 siswa kelas X-MIPA materi gaya dan gerak. Hasil pengamatan menunjukkan kemampuan argumentasi konsep gaya dan gerak pada siswa masih sangat rendah. Kemampaun argumentasi ilmiah yang rendah juga dipengaruhi oleh model pembelajaran yang kurang tepat. Model pembelajaran yang diterapkan adalah model pembelajaran kontekstual berbasis multirepresentasi. Hasil penelitian menunjukkan ada peningkatan kemampuan argumentasi ilmiah setelah menerapkan model pembelajaran kontekstual berbasis multirepresentasi. Analisis yang diperoleh 0% pada level 1, 17.18 % pada level 2, 43.75% pada level 3, 37.13% pada level 4 dan 10.94% pada level 5.